Hubungan indeks massa tubuh (IMT) dengan prestasi belajar pada siswa sekolah menengah atas (SMA) negeri di Kota Denpasar Utara - Mona Mentari Pagi Surbakti; I Made Pande Dwipayana (Universitas Udayana, 2018)
The current global is the problem of obesity, especially Indonesia. In this case the alleged obesity has an effect indirectly, namely the decline in cognitive resulting from an increase in fatty deposits, leading to learning disorders and academic achievement. This study aims to determine body mass index and academic achievement in public high school students in the city of Denpasar. This study was cross-sectional study. The population in this study are students of class IX - IPA 2014/2015 school year at high schools in Denpasar North. This research was conducted in August and September. Used as a sample of 150 students. The data obtained were analyzed with pearson correlation test. Pearson correlation test is used to determine the correlation of body mass index and academic achievement. The results showed body mass index (BMI) in category overweight/obesity is 30,7% and the learning achievement in category standard is 1,0%. In the analysis, 150 samples obtained showed p = 0,244, meaning that there is no significant relationship between BMI and academic achievement (p> 0,05). It can be inferred that the BMI in the State high school students in the city of North Denpasar was no significant relationship between nutritional status and study achievement. Keywords: Body Mass Indeks, Academic Achievement, Obesity